Attitudes of Obstetric and Gynecologic Residents Toward Abortion - Mascovich, Paul R. (1973)
As a follow-up to Wolf's study of attitudes of obstetrical housestaff toward therapeutic abortion,(5) the attitudes of 48 obstetrical residents in the San Francisco Bay area were evaluated by questionnaire and structured interview. Specific issues studied were: (1) Willingness to perform therapeutic abortion, (2) impact of therapeutic abortion on Resident Training Program, (3) attitudes toward different operational procedures, and (4) preferred physician-patient relationship with therapeutic abortion patients. Findings suggest that although there is recognition and acceptance by most residents of the social need for therapeutic abortion, considerable ambivalence persists.